Clinical impact of transcatheter atrial septal defect closure on new onset atrial fibrillation in adult patients: Comparison with surgical closure. Issue 1 (July 2020) - Fujii, Yasuhiro; Akagi, Teiji; Nakagawa, Koji; Takaya, Yoichi; Eto, Koki; Kuroko, Yosuke; Kotani, Yasuhiro; Ejiri, Kentaro; Ito, Hiroshi; Kasahara, Shingo
Highlights: This study was conducted with a specific patient population Incidence of new onset atrial fibrillation (AF) after atrial septal defect (ASD) closure is low even in patients aged ≥40 years A large ASD is a risk factor for new onset AF Catheter closure had lower incidence of AF than surgical closure Abstract: Background: Previous studies demonstrated that the incidence of atrial fibrillation (AF) was significantly increased when patients aged ≥40 years had surgical atrial septal defect (ASD) closure (sASD). However, limited information is available on such findings in transcatheter ASD closure (tASD). The purpose of this study was to investigate the incidence of newly developed AF after tASD in patients aged ≥40 years in whom preoperative AF or atrial flutter (AFL) had not been detected and to compare with the incidence after sASD. Methods: The medical records of patients aged ≥40 years without a history of AF or AFL who underwent tASD (n = 281) or sASD (n = 24) were reviewed. Patients who had catheter ablation before the ASD closure were excluded. Patients with a patent foramen ovale were also excluded. The incidence of newly developed AF after ASD closure and the risk factors for that were evaluated statistically. Results: Eleven patients had newly developed AF (5 in tASD and 6 in sASD) postoperatively including 6 persistent AF (3 each after tASD and sASD). The cumulative incidence of newly developed AF was 0.7% in tASD and 16.7% in sASD, and 2.7% and 20.8% at 1 and 5 years, respectively ( p  < 0.001). ASD diameter ≥30 mm and sASD were potential risk factors for newly developed AF after ASD closure and postoperative persistent AF. Conclusions: In patients aged ≥40 years without a history of AF or AFL, the incidence of newly developed AF after tASD closure was lower than that after sASD. A large ASD more than 30 mm diameter was a potential risk factor for development of AF even if it is closed by transcatheter procedure. Further long-term evaluation after tASD is required to clarify preventive benefit for new onset AF in adult ASD population.